Cultura organizacional y su incidencia en el desempeño laboral en el Conservatorio Ángel Efraín Suárez Carrera de la Ciudad de Babahoyo, periodo 2023. - Mosquera Magallanes, Maribel Magaly (2024)
The Angel Efrain Suarez Carrera Conservatory of the City of Babahoyo is an educational institution belonging to the public sector, which offers Complementary High School in Arts, to carry out the optimal fulfillment of these functions, it is necessary to implement an organizational culture, which serves as a guide to the qualified human talent of this outstanding institution. The objective of this study is to determine how the organizational culture influences the work performance of the staff of the Angel Efrain Suarez Carrera Conservatory of the City of Babahoyo, period 2023. The deductive method is used, as well as a mixed or quali-quantitative research. The results have allowed recognizing that the mission and vision of the institution are moderately present during the development of the activities, the work environment is not entirely positive, although the staff does not consider it as terrible; it was evidenced that the value that is rescued from the development of coexistence is respect, and the scarce communication has not allowed fluidity in interpersonal relationships. The lack of work incentives has led to a lack of work motivation. Through the sources consulted, it was concluded that organizational culture contains determining elements for the management of activities, such as the work environment, the raison d'être of the organization, as well as values and objectives. The study showed that the implementation of organizational culture strategies does have an impact on work performance, as well as the personnel's willingness to get involved in the measures taken for this purpose.